2011
DOI: 10.1111/j.1095-8312.2011.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic traits of westslope cutthroat trout, introduced rainbow trout and their hybrids in an ecotonal hybrid zone along an elevation gradient

Abstract: In the Upper Oldman River, Alberta, introduced non-native hatchery rainbow trout (Oncorhynchus mykiss) hybridize with native westslope cutthroat trout (O. clarkii), resulting in a hybrid swarm. Rainbow trout dominate at low elevations (< 1250 m) in the river mainstem, cutthroat in high-elevation tributaries (> 1400 m), and hybrids are numerically dominant in the mid-elevation range. We hypothesized that metabolism of rainbow trout would exceed that of cutthroat trout, and that the elevation gradient in genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 92 publications
4
38
0
Order By: Relevance
“…Across riverscapes, RBT Â WCT hybridization is often prevalent in low elevation streams with warmer water temperatures, whereas non-hybridized populations occur in colder, headwater streams [25,26]. This led to the hypothesis that cold temperatures in headwater streams impart a competitive advantage to native WCT [27,28]. We found evidence for selection against RBT admixture in two streams with contrasting thermal characteristics; Cyclone Creek is considerably warmer than Langford Creek but has a much lower pRBT.…”
Section: (B) Antagonisms Between Selection and Dispersalmentioning
confidence: 83%
“…Across riverscapes, RBT Â WCT hybridization is often prevalent in low elevation streams with warmer water temperatures, whereas non-hybridized populations occur in colder, headwater streams [25,26]. This led to the hypothesis that cold temperatures in headwater streams impart a competitive advantage to native WCT [27,28]. We found evidence for selection against RBT admixture in two streams with contrasting thermal characteristics; Cyclone Creek is considerably warmer than Langford Creek but has a much lower pRBT.…”
Section: (B) Antagonisms Between Selection and Dispersalmentioning
confidence: 83%
“…Westslope cutthroat trout with some level of admixture of RT alleles grow more quickly and mature faster than nonadmixed WSCT, and a trade-off exists between metabolic scope (RT) and growth efficiency (WSCT) such that RT are favoured at high temperatures by their increased metabolic scope and WSCT are favoured at low water temperatures by increased growth efficiency (Rasmussen et al 2010). Subsequently, Rasmussen et al (2012) documented interspecific differences in metabolism in terms of rates of oxygen consumption, and the activity of metabolically relevant enzymes, lactate dehydrogenase and citrate synthase, and concluded that fish with RT alleles tended to have higher metabolic demands than fish comprised primarily of a WSCT genomic background. Hybrids generally had intermediate metabolic traits and were better able to balance the trade-off between energetic scope and growth efficiency, allowing them to be successful in cooler, more upstream locations than RT (Rasmussen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Rasmussen et al (2012) documented interspecific differences in metabolism in terms of rates of oxygen consumption, and the activity of metabolically relevant enzymes, lactate dehydrogenase and citrate synthase, and concluded that fish with RT alleles tended to have higher metabolic demands than fish comprised primarily of a WSCT genomic background. Hybrids generally had intermediate metabolic traits and were better able to balance the trade-off between energetic scope and growth efficiency, allowing them to be successful in cooler, more upstream locations than RT (Rasmussen et al 2012). Consequently, nonadmixed WSCT may be observed to persist predominately in high-elevation tributaries as a function of the physiological and metabolic limitations of RT and interspecific hybrids in these habitats (Rasmussen et al 2010(Rasmussen et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations